Determination of Radon Concentrations in AL-NAJAF Governorate by Using Nuclear Track Detector CR-39 - Tawfiq, Nada F; Nasir, Hussein M; Khalid, Rafaat (Al-Nahrain Journal of Science, 2018)
Appeared different cases of cancer in certain districts in Al-Najaf governorate and it had assumed several hypotheses. Including the existence of radon in the air inside homes, where the radon gas is the largest and the most important variables contributing to the exposure to natural radiation in the world. Radon cup technique was used, which is a cylindrical chamber 5 cm in diameter and height of 7 cm inside the detector impact in solid state nuclear track detector CR-39 and these detectors was etched with 6.25 N from sodium hydroxide at a temperature of 70o C in a time of 12 hours. Values of radon concentrations ranged between 74.2804 ± 42.6048 Bq/m3 to 478.1301 ± 53.325 Bq/m3, also found that the rate of radon concentration in Al-Najaf governorate, up to 183.682 Bq/m3 with standard deviation of up to 104.231 Bq/m3. High cancer rates in some neighborhoods in Al-Najaf governorate can be attributed to high concentrations of radon gas in these areas.